Low-shrinkage antistatic color master batch, PBT loose tube, optical cable containing PBT loose tube and production method of optical cable
By using PET as a carrier, the low-shrinkage antistatic color masterbatch combined with carbon nanotubes and additives, the PBT loose sleeve excess length control and electrostatic problems are solved, the optical cable production efficiency and quality are improved, and the strength and toughness of the loose sleeve are enhanced.
Patent Information
- Application Number
- CN202510000062.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-01
- Publication Date
- 2025-03-28
AI Technical Summary
现有用于PBT松套管的色母粒干扰松套管余长控制且存在静电问题,影响光缆生产效率和质量。
Low-contraction antistatic color masterbatches using PET as carrier, and carbon nanotubes are added as antistatic agents and additives to reduce the shrinkage and static electricity of the loose sleeve.
It effectively reduces the shrinkage of the loose sleeve, balances the residual length deviation caused by the addition of masterbatch, improves the production efficiency and quality of optical cables, and improves the strength and toughness of the PBT loose sleeve.
Smart Images

Figure CN119708781A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of masterbatches, and more specifically, relates to low-shrinkage antistatic masterbatches, PBT loose tubes, optical cables containing the same, and production methods thereof. Background Art
[0002] In the production process of stranded optical cables, loose tubes of different colors are produced according to the color spectrum, which not only helps with identification and management in production and actual use, but also meets the needs of aesthetics, safety and market. Usually, loose tubes are colored by masterbatches of different colors during the production process of optical cables, which has the advantages of simple operation and no pollution to the environment. However, in the actual production process, the tube material PBT is a semi-crystalline material. The addition of masterbatches is equivalent to the continuous addition of heterogeneous nucleating agents, which significantly increases the crystallization rate and crystallinity of PBT, and ultimately interferes with the control of the excess length of the loose tube. In order to ensure the quality of the optical cable and the mechanical, temperature and other properties of the optical cable, most optical cable factories reduce the production speed or formulate a separate process to reduce the shrinkage of the loose tube, thereby controlling the stability of the excess length. This seriously affects the production efficiency and quality of the optical cable, and restricts the development of the industry.
[0003] At the same time, masterbatches often aggregate due to static electricity, resulting in poor dispersion in the main material and easy adhesion in the material tank or hopper, causing moisture or color mixing; static electricity can also cause masterbatches to absorb dust and impurities in the air, causing loose tubes to bulge. In addition, the agglomeration effect of masterbatches can also reduce the strength and toughness of the loose tubes. Summary of the invention
[0004] In view of the defects of the prior art, the present application provides a low-shrinkage antistatic masterbatch, a PBT loose tube, an optical cable containing the same and a production method thereof, aiming to solve the problem that the existing masterbatch for PBT loose tube interferes with the control of the excess length of the loose tube and has static electricity.
[0005] According to one aspect of the present application, a low shrinkage antistatic masterbatch is provided, comprising PET, carbon nanotubes, pigments and additives, wherein the PET is used as a carrier to reduce the shrinkage rate of the PBT loose tube, and the carbon nanotubes are used as an antistatic agent to reduce the static electricity of the masterbatch.
[0006] Through the above technical scheme conceived by the present application, compared with the prior art, since the present application adopts PET as the carrier of the masterbatch, the shrinkage of the loose tube can be reduced to balance the problem of the excessive length of the PBT loose tube caused by the addition of the masterbatch, and at the same time, the electrostatic effect of the masterbatch can be reduced in combination with carbon nanotubes, thereby achieving low shrinkage and anti-static effects.
[0007] As a further preferred embodiment, based on weight parts, the low shrinkage antistatic masterbatch contains 60 to 70 parts of PET, 15 to 20 parts of carbon nanotubes, 10 to 20 parts of pigments, and 10 to 23 parts of additives.
[0008] As further preferred, the auxiliary agent includes one or more of a nucleating agent, a surface treatment agent, an antioxidant, a moisture-proof additive, and a dispersant.
[0009] As further preferred, the auxiliary agent includes a nucleating agent, a surface treatment agent, an antioxidant, a moisture-proof additive and a dispersant. In terms of weight parts, the auxiliary agent includes 2 to 5 parts of nucleating agent, 4 to 8 parts of surface treatment agent, 2 to 4 parts of antioxidant, 1 to 3 parts of moisture-proof additive, and 1 to 3 parts of dispersant.
[0010] As further preferred, the auxiliary agent also includes 1 to 3 parts of a lubricant, and the lubricant is one or both of stearic acid and butyl stearate.
[0011] As further preferred, the nucleating agent is one or more of talc, silicon dioxide, and mica; the surface treatment agent is one or both of titanate coupling agent and zinc stearate; the antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 264; the moisture-proof additive is one or both of tin oxide and calcium oxide; the dispersant is one or more of polyethylene wax, sulfonating agent, and ethylene bis stearamide, and / or, The pigment is an inorganic pigment and / or an organic pigment.
[0012] According to another aspect of the present application, a method for producing the low shrinkage antistatic masterbatch is provided, which specifically comprises: S1: dispersing the additive in a solution, then adding carbon nanotubes into the solution to adsorb the additive so that the additive covers the surface of the carbon nanotubes, and then drying the solution to obtain a precursor mixture; S2: mixing the precursor mixture with PET and pigment and then granulating to obtain the low shrinkage antistatic masterbatch.
[0013] As further preferred, in step S2, the precursor mixture, PET and pigment are mixed and plasticized before granulation.
[0014] According to another aspect of the present application, a PBT loose tube prepared using the low shrinkage antistatic masterbatch is provided.
[0015] According to another aspect of the present application, an optical cable is provided, comprising the above-mentioned PBT loose tube and an optical fiber arranged inside the PBT loose tube.
[0016] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art: 1. The low shrinkage antistatic masterbatch for PBT loose tube provided by the present application adopts PET as a carrier, which can reduce the shrinkage of the loose tube to balance the problem of excessive length of the PBT loose tube caused by the addition of the masterbatch, and does not need to reduce the production speed or specify a separate process to control the stability of the excess length, effectively improving the production rate and quality of the optical cable, and the PBT / PET alloy produced in the generated loose tube has excellent properties such as high strength, good rigidity, high heat deformation temperature, good dimensional stability, and good surface gloss. At the same time, the present application adopts carbon nanotubes as an antistatic agent to improve the conductivity of the masterbatch to reduce static electricity, and the carbon nanotubes can also significantly improve the strength and toughness of the PBT loose tube; 2. In particular, the present application optimizes the content of each component in the low shrinkage antistatic masterbatch, thereby ensuring good compatibility while avoiding insufficient chroma or poor antistatic effect, and also ensuring good dispersion of carbon nanotubes; 3. At the same time, the method for producing low shrinkage antistatic masterbatch provided by the present application can effectively solve the problem that carbon nanotubes are easy to form agglomerates, thereby affecting their dispersibility in masterbatch and masterbatch processing performance, by dispersing the additives in the solution so that they can be adsorbed with carbon nanotubes to form a film covering the surface of the carbon nanotubes, and then drying and granulating. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a production flow chart of low shrinkage antistatic masterbatch for PBT loose tube provided in an embodiment of the present application. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0019] According to one aspect of the present application, a low shrinkage antistatic masterbatch is provided, comprising PET, carbon nanotubes, pigments and additives, wherein: PET is used as a carrier. Since PET and PBT have similar solubility parameters and chemical structures, the mixed system of the two has good compatibility and only one glass transition temperature appears. Therefore, PET can be used as a carrier of masterbatch for PBT loose tubes. At the same time, the crystallization performance of PET is not as good as that of PBT. Therefore, using PET as a carrier can avoid the problem that the crystallization rate and crystallization speed of PBT are significantly increased due to the addition of masterbatch, thereby reducing the shrinkage of the loose tube, and then balancing the problem of large excess length of the PBT loose tube caused by the addition of masterbatch. In addition, the addition of PET can interact with PBT to form a PBT / PET alloy, and the PBT / PET alloy has excellent properties such as high strength, good rigidity, high heat deformation temperature, good dimensional stability, and good surface gloss. As an antistatic agent, carbon nanotubes have good electrical conductivity and can increase the conductivity of masterbatch to reduce the generation and accumulation of static electricity, making it easier to leak static electricity, thereby reducing the harm of static electricity. At the same time, carbon nanotubes have extremely high strength and modulus. The addition of carbon nanotubes can significantly improve the strength and toughness of PBT loose tubes, which is actually manifested in increasing the pressure resistance of PBT loose tubes. In addition, carbon nanotubes have excellent thermal conductivity and can improve the thermal stability and heat resistance of PBT loose tubes.
[0020] Therefore, the present application adopts PET as the carrier of the masterbatch, which can reduce the shrinkage rate of the PBT loose tube to balance the problem of the excessive length of the PBT loose tube caused by the addition of the masterbatch, and there is no need to reduce the shrinkage of the loose tube by reducing the production speed, which effectively improves the production efficiency and quality of the optical cable. At the same time, the electrostatic effect of the masterbatch is reduced by cooperating with carbon nanotubes to avoid the agglomeration of the masterbatch and reduce the strength and toughness of the loose tube, thereby achieving the effects of low shrinkage and anti-static.
[0021] Furthermore, in terms of weight, the low shrinkage antistatic masterbatch contains 60 to 70 parts of PET, 15 to 20 parts of carbon nanotubes, 10 to 20 parts of pigments, and 10 to 23 parts of additives. Through the interaction of the contents of PET, carbon nanotubes, pigments, and additives, it is possible to ensure good compatibility while avoiding insufficient chroma or poor antistatic effect, and at the same time ensure good dispersion of carbon nanotubes.
[0022] Furthermore, the auxiliary agent includes one or more of a nucleating agent, a surface treatment agent, an antioxidant, a moisture-proof additive, and a dispersant. In the actual production process, the composition of the auxiliary agent can be determined in combination with production needs and production costs. For example, the auxiliary agent only includes a nucleating agent and a dispersant, or the auxiliary agent includes a nucleating agent, a surface treatment agent, and a dispersant.
[0023] More preferably, the additives include nucleating agent, surface treatment agent, antioxidant, moisture-proof additive and dispersant. According to weight parts, the nucleating agent is 2 to 5 parts, the surface treatment agent is 4 to 8 parts, the antioxidant is 2 to 4 parts, the moisture-proof additive is 1 to 3 parts, and the dispersant is 1 to 3 parts. Among them, the nucleating agent is one or more of talc, silica, and mica, the surface treatment agent is one or two of titanate coupling agent and zinc stearate, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 264, the moisture-proof additive is one or two of tin oxide and calcium oxide, and the dispersant is one or more of polyethylene wax (PE), sulfonating agent, and ethylene bis stearamide (EBS).
[0024] Furthermore, the additive also includes 1 to 3 parts of a lubricant, which is used to reduce the adhesion between particles and promote the sliding between particles, thereby increasing the fluidity of the masterbatch and improving the pigment dispersibility. The lubricant is one or both of stearic acid and butyl stearate.
[0025] Furthermore, the pigment is an inorganic dye such as titanium dioxide (titanium dioxide) + carbon black, cadmium yellow, cadmium red, iron blue, or an organic dye such as phthalocyanine green and fast red.
[0026] According to another aspect of the present application, Figure 1 As shown, a method for producing the above-mentioned low shrinkage antistatic masterbatch is provided, which specifically comprises: S1: dispersing the additive in a solution, then adding carbon nanotubes into the solution to adsorb the additive so that the additive covers the surface of the carbon nanotubes, and then drying the solution to obtain a precursor mixture, wherein the precursor mixture includes the pre-treated carbon nanotubes and the remaining additive; S2 mixes the precursor mixture with PET and pigment and then granulates it through a twin-screw extruder to produce low shrinkage antistatic masterbatch.
[0027] The present application takes into account that carbon nanotubes have a relatively high long diameter and are prone to form agglomerates, thereby affecting their dispersibility in the masterbatch and the processing performance of the masterbatch. At the same time, compared with the prior art that uses PBT as a carrier, the dispersion effect of using PET as a carrier is inferior to that of PBT. Therefore, the present application proposes to pre-treat the carbon nanotubes before granulation, adsorb the additives and carbon nanotubes in the solution to form a thin film covering the surface of the carbon nanotubes to obtain pre-treated carbon nanotubes, thereby preventing the carbon nanotubes from forming agglomerates in the subsequent granulation process, which would affect the performance of the low-shrinkage antistatic masterbatch.
[0028] Furthermore, in step S2, the precursor mixture, PET and pigment are fully wetted in an internal mixer for mixing and plasticizing, and then sent to a twin-screw extruder for granulation.
[0029] According to another aspect of the present application, a PBT loose tube prepared using the above-mentioned low shrinkage antistatic masterbatch is provided, wherein the low shrinkage antistatic masterbatch is used to color the PBT loose tube and the excess length of the PBT loose tube can be better controlled.
[0030] According to another aspect of the present application, an optical cable is provided, comprising the above-mentioned PBT loose tube and an optical fiber arranged inside the PBT loose tube.
[0031] The technical solution provided in this application is further described below based on specific embodiments.
[0032] Example 1 (a) weighing 65 parts of PET, 18 parts of carbon nanotubes, 15 parts of pigments and 20 parts of additives, wherein the additives, by weight, include 2 parts of talc as a nucleating agent, 5 parts of zinc stearate as a surface treatment agent, 2 parts of antioxidant 1010, 3 parts of tin oxide as a moisture-proof additive and 1 part of polyethylene wax as a dispersant; (b) dispersing the additive in a solution, then adding carbon nanotubes into the solution to allow the additive to adsorb to the carbon nanotubes, so that the additive covers the surface of the carbon nanotubes, and then filtering and drying to obtain the pre-treated carbon nanotubes and the remaining additive; (c) The pre-treated carbon nanotubes, the remaining additives, the PET and the pigment are fed into an internal mixer for full impregnation, and then pelletized by a twin-screw extruder to obtain a low shrinkage antistatic masterbatch.
[0033] Example 2 (a) 70 parts of PET, 20 parts of carbon nanotubes, 20 parts of pigments and 15 parts of additives are weighed, wherein the additives include 4 parts of nucleating agent mica, 6 parts of surface treatment agent titanate coupling agent, 4 parts of antioxidant 1076, 1 part of moisture-proof additive calcium oxide and 3 parts of dispersant sulfonating agent, according to weight parts; (b) dispersing the additive in a solution, then adding carbon nanotubes into the solution to allow the additive to adsorb onto the carbon nanotubes, so that the additive covers the surface of the carbon nanotubes, and then filtering and drying to obtain pre-treated carbon nanotubes; (c) The pre-treated carbon nanotubes, PET and pigment are fed into an internal mixer for full impregnation, and then pelletized by a twin-screw extruder to obtain a low shrinkage antistatic masterbatch.
[0034] Example 3 According to weight, 60 parts of PET, 15 parts of carbon nanotubes, 10 parts of pigments and 10 parts of additives are weighed, wherein the additives, according to weight, include 5 parts of nucleating agent silicon dioxide, 4 parts of surface treatment agent zinc stearate, 3 parts of antioxidant 1076, 1 part of moisture-proof additive tin oxide, 2 parts of EBS dispersant, and 1 part of lubricant butyl stearate; the additives are dispersed in a solution, and then carbon nanotubes are added to the solution to adsorb the additives so that the additives cover the surface of the carbon nanotubes, and then filtered and dried to obtain pre-treated carbon nanotubes; the pre-treated carbon nanotubes, PET and pigments are sent to an internal mixer for full infiltration, and then granulated by a twin-screw extruder to obtain low-shrinkage antistatic masterbatch. Example 4 (a) weighing 68 parts of PET, 16 parts of carbon nanotubes, 17 parts of pigments and 23 parts of additives, wherein the additives, by weight, include 3 parts of nucleating agent mica, 8 parts of surface treatment agent titanate coupling agent, 4 parts of antioxidant 264, 2 parts of moisture-proof additive), 1 part of dispersant sulfonating agent and 3 parts of lubricant stearic acid; (b) dispersing the additive in a solution, then adding carbon nanotubes into the solution to allow the additive to adsorb onto the carbon nanotubes, so that the additive covers the surface of the carbon nanotubes, and then filtering and drying to obtain pre-treated carbon nanotubes; (c) The pre-treated carbon nanotubes, PET and pigment are fed into an internal mixer for full impregnation, and then pelletized by a twin-screw extruder to obtain a low shrinkage antistatic masterbatch.
[0035] Comparative Example 1 The same as Example 1, only in step (a), PET is replaced by PBT, so that PBT is used as a carrier of the masterbatch to prepare the PBT masterbatch.
[0036] The low shrinkage antistatic masterbatch prepared in Example 1 and the PBT masterbatch prepared in Comparative Example 1 were applied to the production of PBT loose tubes at an addition ratio of 3% to obtain optical cables A and B. The optical fiber length and tube length of optical cables A and B were measured. The optical fiber length of optical cable A was 8795 mm, the tube length was 8792 mm, and the excess length was 0.34‰. The optical fiber length of optical cable B was 9674 mm, the tube length was 9665 mm, and the excess length was 0.93‰.
[0037] By comparing the excess length of optical cable A and optical cable B, it can be seen that using PET as a carrier can effectively reduce the shrinkage of the loose tube to reduce the excess length, without the need to reduce the production speed or specify a separate process to control the stability of the excess length.
[0038] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. Low shrinkage antistatic masterbatch, characterized by: The invention comprises PET, carbon nanotubes, pigments and additives, wherein the PET is used as a carrier to reduce the shrinkage rate of the PBT loose tube, and the carbon nanotubes are used as an antistatic agent to reduce the static electricity of the masterbatch.
2. The low shrinkage antistatic masterbatch according to claim 1, characterized in that: In terms of weight, the low shrinkage antistatic masterbatch contains 60 to 70 parts of PET, 15 to 20 parts of carbon nanotubes, 10 to 20 parts of pigments, and 10 to 23 parts of additives.
3. The low shrinkage antistatic masterbatch according to claim 1, characterized in that: The auxiliary agent includes one or more of a nucleating agent, a surface treatment agent, an antioxidant, a moisture-proof additive, and a dispersant.
4. The low shrinkage antistatic masterbatch according to claim 3, characterized in that: The auxiliary agents include nucleating agents, surface treatment agents, antioxidants, moisture-proof additives and dispersants. In terms of weight parts, the auxiliary agents include 2 to 5 parts of nucleating agents, 4 to 8 parts of surface treatment agents, 2 to 4 parts of antioxidants, 1 to 3 parts of moisture-proof additives and 1 to 3 parts of dispersants.
5. The low shrinkage antistatic masterbatch according to claim 4, characterized in that: The auxiliary agent also includes 1 to 3 parts of a lubricant, and the lubricant is one or both of stearic acid and butyl stearate.
6. The low shrinkage antistatic masterbatch according to claim 3, characterized in that: The nucleating agent is one or more of talc, silicon dioxide, and mica; the surface treatment agent is one or both of titanate coupling agent and zinc stearate; the antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 264; the moisture-proof additive is one or both of tin oxide and calcium oxide; the dispersant is one or more of polyethylene wax, sulfonating agent, and ethylene bis stearamide, and / or, The pigment is an inorganic pigment and / or an organic pigment.
7. The method for producing low shrinkage antistatic masterbatch according to any one of claims 1 to 6, characterized in that: Specifically include: S1: dispersing the additive in a solution, then adding carbon nanotubes into the solution to adsorb the additive so that the additive covers the surface of the carbon nanotubes, and then drying the solution to obtain a precursor mixture; S2: mixing the precursor mixture with PET and pigment and then granulating to obtain the low shrinkage antistatic masterbatch.
8. The production method according to claim 7, characterized in that In step S2, the precursor mixture, PET and pigment are mixed and plasticized before granulation.
9. A PBT loose tube prepared using the low shrinkage antistatic masterbatch as claimed in any one of claims 1 to 6.
10. An optical cable, characterized in that: The invention comprises the PBT loose tube as claimed in claim 9 and an optical fiber arranged inside the PBT loose tube.